Expanding the Horizons of Supply Chain in Higher Education Institution: Resources and Expatriate Academics (EAs) Outcomes - Subramaniam Sri Ramalu; Chandrakantan Subramaniam; Gunalan Nadarajah (International Journal of Supply Chain Management, 2018)
The ultimate goal of any service industry is to provide quality services to its customers. Applying industry models of supply chain management in higher education institutions (HEIs), this study aims to examine the impact of various resources on expatriate academics outcomes. Internationalisation of higher education sector has created the need to recruit foreign faculty to become part of critical inputs in providing world-class education to students. In this regard, understanding the factors contribute to their effectiveness is imperative for continuous quality improvement. A survey-based quantitative research using a sample of 152 expatriate academics (EAs) employed in 20 Malaysian public universities revealed some important findings. Both the personal (cultural intelligence) and organizational resources (perceived organizational support) are found to be important determinants of EAs work engagement and psychological needs satisfaction which is important for quality service delivery. The findings of this study have made significant contribution to international human resource management practices and policy makers especially to Malaysian HEIs with regards to recruitment and retention of academic expatriates.